History and Development of Jazz Music - Tashxodjayev, Botir (Research Parks Publishers, 2023)
This article is devoted to the history of creation and stages of development of jazz music, the emergence of Gospel, Spiritual, Ragtime, Blues, Dixieland jazz styles and their founders are described in detail.